Topic Modeling based on Louvain method in Online Social Networks - Kido, Guilherme Sakaji; Igawa, Rodrigo Augusto; Barbon Jr., Sylvio (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2016: Anais do XII Simpósio Brasileiro de Sistemas de Informação, 2016)
Online Social Networks (OSNs) are the most used media nowadays, such as Twitter. The OSNs provide valuable information to marketing and competitiveness based on users posts and opinions stored inside huge volume of data from several themes, topics and subjects. In order to mining the topics discussed on an OSN we present a novel application of Louvain method for Topic Modeling based on communities detection in graphs by modularity. The proposed approach succeeded in finding topics in five different datasets composed of textual content from Twitter and Youtube. Another important contribution achieved was about the presence of texts posted by spammers. In this case, a particular behavior observed by graph architecture (density and degree) allows the classification of a topic as natural or artificial, this last created by the spammers on OSNs.